Global implementation survey of Integrated Management of Childhood Illness (IMCI): 20 years on. Issue 7 (30th July 2018) - Boschi-Pinto, Cynthia; Labadie, Guilhem; Dilip, Thandassery Ramachandran; Oliphant, Nicholas; Dalglish, Sarah L; Aboubaker, Samira; Agbodjan-Prince, Olga Adjoa; Desta, Teshome; Habimana, Phanuel; Butron-Riveros, Betzabe; Al-Raiby, Jamela; Siddeeg, Khalid; et al.
Abstract : Objective: To assess the extent to which Integrated Management of Childhood Illness (IMCI) has been adopted and scaled up in countries. Setting: The 95 countries that participated in the survey are home to 82% of the global under-five population and account for 95% of the 5.9 million deaths that occurred among children less than 5 years of age in 2015; 93 of them are low-income and middle-income countries (LMICs). Methods: We conducted a cross-sectional self-administered survey. Questionnaires and data analysis focused on (1) giving a general overview of current organisation and financing of IMCI at country level, (2) describing implementation of IMCI's three original components and (3) reporting on innovations, barriers and opportunities for expanding access to care for children. A single data file was created using all information collected. Analysis was performed using STATA V.11. Participants: In-country teams consisting of representatives of the ministry of health and country offices of WHO and Unicef. Results: Eighty-one per cent of countries reported that IMCI implementation encompassed all three components. Almost half (46%; 44 countries) reported implementation in 90% or more districts as well as all three components in place (full implementation). These full-implementer countries were 3.6 (95% CI 1.5 to 8.9) times more likely to achieve Millennium Development Goal 4 than other (not full implementer) countries. Despite these high reported implementation rates, the strategy is not reaching the children who need it most, as implementation is lowest in high mortality countries (39%; 7/18). Conclusion: This survey provides a unique opportunity to better understand how implementation of IMCI has evolved in the 20 years since its inception. Results can be used to assist in formulating strategies, policies and activities to support improvements in the health and survival of children and to help achieve the health-related, post-2015 Sustainable Development Goals.